The Elephant Curve of Global Inequality and Growth - Gonzalez Alvaredo, Facundo (2018)
The dynamics of global inequality have attracted growing attention in recent years (Piketty 2014). However, we still know relatively little about how the distribution of global income is evolving. Income inequality is increasing in many countries, but large emerging countries like India and China are catching up and might drive global inequality down. Recent studies of global inequality combine household surveys and provide valuable estimates (Lakner and Milanovic 2016; Liberati 2015; Ortiz and Cummins 2011). Surveys, however, are not uniform across countries, they cannot capture top incomes well, and are not consistent with macroeconomic totals. In this paper, we report on new estimates of global inequality presented in the World Inequality Report 2018 (Alvaredo et al. 2018). These estimates are based on recent, homogeneous inequality statistics produced for a number of countries in the World Inequality Database (WID.world). We find that the global top 1 percent has captured twice as much total growth than the global bottom 50 percent between 1980 and 2016. We also analyze different projected trajectories for global inequality in the coming decades.